Dragonfly wing venous cross-joints inspire the design of higher-performance bolted timber truss joints. (15th February 2016) - Fauziyah, S.; Soesilohadi, R.C.H.; Retnoaji, B.; Alam, P.
Abstract: This communication concerns the design and development of high performance biomimetic timber joints as inspired by the venous cross-joints of dragonfly wings. A special cross-joint configuration in Crocothemis servilia from the Libellulid family is identified. Between the veins of this cross-joint is a resilin envelope. Finite element modelling reveals that the presence of this resilin envelope reduces the levels of localised stress in the jointing region. By gaining an understanding of the structure and function of this dragonfly wing joint, dragonfly-joint inspired timber trusses are developed by integrating low-modulus adhesives around bolted connectors. We find that not only are the properties of strength, stiffness, toughness and deformability of bolted truss joints vastly improved on applying dragonfly-mimicking technology, but that the fatigue resistance is also enhanced. This preliminary work is an important step forward in the design and development of high-performance biomimetic joints for timber construction.